Relation of Hyperprolactinemia with Inflammation and Biochemical Characteristics in Women with Polycystic Ovary Syndromes (PCOS) - Abdullah, Mustafa Riyadh; Alabassi, Hazima Mossa (Iraqi Journal of Science, 2025)
Since high prolactin levels worsen Polycystic Ovary Syndrome (PCOS) symptoms, they have been the focus recently. The current study aims to shed light on hyperprolactinemia and the role of inflammation and biochemical disturbances in increasing the severity of PCOS. The study involved 90 participants: 68 women with PCOS, aged between 20-45, and 22 apparently healthy women with age match to patients. Blood samples were collected for biochemical analysis, utilizing ElectroChemiLuminescence, ELISA, and NycoCardTM techniques for precise measurement of prolactin, testosterone, estrogen, TSH, FSH, LH, anti-FSH, and CRP. Depending on the prolactin level, samples were categorized into 3 groups: hyperprolactinemia-PCOS (above 23.30 ng/ml), normal prolactin PCOS, and normal prolactin without PCOS. PCOS recorded a significant increase in prolactin level compared with control at p-value (<0.0001). Also, PCOS with hyperprolactinemia displayed notably higher levels of estrogen and CRP compared to both the normal prolactin PCOS and control at p-value (<0.0001). Additionally, PCOS with hyperprolactinemia exhibited notably higher levels of TSH compared to the control at p-value (<0.0001). Also, a significant difference was found in the level of testosterone, LH, LH/FSH ratio, and anti-FSH in PCOS compared to control at p-value (<0.0001). Based on the current study, which showed a statistically significant relationship between hyperprolactinemia and high levels of inflammation as an immune reaction accompanied by hormonal disorders and high levels of anti-FSH, it can be concluded that all the factors mentioned in this study should be included in PCOS treatment strategies to restore hormonal and immune balance, which may be a cause of the condition.